Inovação violenta? STEM por uma perspectiva de gênero - Lopes, Amanda Santos (2023)
This article addresses the issue of gender inequality in the context of Industry 4.0, through a literature review on innovation and diffusion, and a qualitative survey of training courses in the programming sector. The study analyzes the inclusion of women in STEM fields and the challenges they face in the high technology industry. It discusses the perspectives and agendas that influence the market and industrial transformation of the 4th Industrial Revolution, while highlighting the importance of female participation in pursuing a more inclusive and innovative system. The paper concludes by emphasizing the need for collective actions and effective policies to ensure equal opportunities and female leadership in the ever-evolving technological landscape